2012
DOI: 10.1177/1753193412451401
|View full text |Cite
|
Sign up to set email alerts
|

Tendon transfer for treatment of internal rotation contracture of the shoulder in brachial plexus birth palsy

Abstract: We retrospectively analyzed 63 patients with internal rotation contracture of the shoulder secondary to brachial plexus birth palsy treated with subscapularis sliding combined with either latissimus dorsi transfer (group A: n = 18) or latissimus dorsi and teres major transfer (group B: n = 45) to the rotator cuff. The mean age at time of surgery was 43 months (SD 21 months; range 8 months to 9 years). We used a modification of the Gilbert shoulder grading system for assessment. All patients showed statisticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…A wide variety of surgical approaches are applied to increase shoulder function in the OBPI, most of which aim to increase shoulder external rotation and abduction by subscapularis and pectoralis major release, tendon transfer of the latissimus dorsi and teres major, and external rotation humeral osteotomy (Bae and Waters, 2007; Naoum et al., 2015; Ozben et al., 2011). However, some shoulder internal rotation loss has been reported as a result of this surgery and is manifested by the child not being able to reach his/her abdomen by his/her hand (Abdel-Ghani et al., 2012; Abdelgawad and Pirela-Cruz, 2014; Sibinski et al., 2012). Since shoulder internal rotation plays a key role in ADL, surgery that leads to a decrease in internal rotation may cause functional impairment and limitations in ADL.…”
Section: Discussionmentioning
confidence: 99%
“…A wide variety of surgical approaches are applied to increase shoulder function in the OBPI, most of which aim to increase shoulder external rotation and abduction by subscapularis and pectoralis major release, tendon transfer of the latissimus dorsi and teres major, and external rotation humeral osteotomy (Bae and Waters, 2007; Naoum et al., 2015; Ozben et al., 2011). However, some shoulder internal rotation loss has been reported as a result of this surgery and is manifested by the child not being able to reach his/her abdomen by his/her hand (Abdel-Ghani et al., 2012; Abdelgawad and Pirela-Cruz, 2014; Sibinski et al., 2012). Since shoulder internal rotation plays a key role in ADL, surgery that leads to a decrease in internal rotation may cause functional impairment and limitations in ADL.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Significant external rotation contracture of the shoulder was experienced in 66.67% of cases but it was more noticed in group B cases. It was concluded that corrective surgery should be restricted to latissimus dorsi transfer without teres major transfer to avoid external rotation contractures [22].…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Unfortunately, this nerve transfer is still not included in recently published MRC management strategies. 3,7 No publication states that significant dysplasia appeared in children with balanced rotation, either after spontaneous recovery or after suprascapular nerve reconstruction, unless we consider the rare cases of congenital humeral head (sub)dislocation. Early restoration of the rotational balance not only increases the functional score and the more "natural" shape of movements (elbow flexion without a trumpet sign), but also should allow a more congruent growth of the GHJ.…”
Section: The Role Of Suprascapular Nerve Neurotizationmentioning
confidence: 99%
“…Recent papers [3][4][5][6][7][8][9] update the common knowledge on this problem and present postoperative results with variable follow-up periods.…”
Section: Introductionmentioning
confidence: 99%